Is home environment associated with child fluid reasoning abilities in middle childhood in high-risk settings? findings from a cross-sectional study in Pakistan - Muneera A. Rasheed; Sondre Aasen Nilsen; Tor A. Strand; Fariha Shaheen; Ingrid Kvestad (BMC, 2024)
Abstract Background Evidence from low- and middle-income countries (LMIC) suggests that home environment is associated with early childhood development outcomes. However, studies from LMIC that have examined how the home environment during middle childhood is associated with intellectual abilities are scarce. The objective of the study was to explore the association between different aspects of the home environment at 7-8 years and fluid reasoning abilities in a rural, high-risk cohort in Pakistan. Methods We employed a cross-sectional research design to examine 1172 children between 7 and 8 years and their families, utilizing the Home Observation for Measurement of Environment for Middle Childhood (HOME-MC) to evaluate various aspects of the home environment and the Fluid Reasoning Index (FRI) of the Wechsler Intelligence for Children (WISC)-5th edition to assess the fluid reasoning abilities of the children. Multivariable regression analyses were used to examine the association between different components of HOME-MC (scored as indices) and FRI scores. Findings Learning materials and opportunities (β = 1.74, 95% CI = 1.15, 2.33) and Responsivity (β = 1.73, 95% CI = 1.07, 2.38) indices had the strongest association with FRI score followed by Family companionship index (β = 1.27, 95% CI = 0.63, 1.90). The eight different indices of the HOME-DC explained 22% of the total variation in FRI scores. Conclusion We conclude that concurrent learning opportunities, parental responsivity and family companionship at home are associated with fluid reasoning abilities during middle childhood which is comparable to what has been found in early childhood years.